2005
DOI: 10.1530/eje.1.01980
|View full text |Cite
|
Sign up to set email alerts
|

Extended clinical phenotype, endocrine investigations and functional studies of a loss-of-function mutation A150V in the thyroid hormone specific transporter MCT8

Abstract: Objective: Thyroid hormones, besides having other functions, are known to be essential for the development of the human brain. Recently the monocarboxylate transporter 8 (MCT8) was identified as a thyroid hormone transporter which is expressed in different regions of the human brain. Here we describe in detail the clinical and biochemical features in response to thyroid hormone administration of a boy carrying an MCT8 mutation (A150V) in the second transmembrane domain. Methods: To study the functional impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
83
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 13 publications
12
83
2
1
Order By: Relevance
“…(14). The patient we have described, like other patients with inactivating mutations of MCT8, had no signs or symptoms typically associated to congenital hypothyroidism (prolonged jaundice, umbilical hernia, bradycardia, growth retardation, myxedema and tendency to overweight or obesity) (12). This clinical finding reinforces the concept that tissues like bone, fat and liver are not as dependent on MCT8 for TH transport as the brain is.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…(14). The patient we have described, like other patients with inactivating mutations of MCT8, had no signs or symptoms typically associated to congenital hypothyroidism (prolonged jaundice, umbilical hernia, bradycardia, growth retardation, myxedema and tendency to overweight or obesity) (12). This clinical finding reinforces the concept that tissues like bone, fat and liver are not as dependent on MCT8 for TH transport as the brain is.…”
Section: Discussionsupporting
confidence: 78%
“…During hypothyroid states it is important that the intracellular concentration of T3, the active TH, be maintained at a safe range, especially in vital organs like the brain. In the brain this is achieved by means of increased brain uptake of serum T3 through increased action of transporters like MCT8, increased conversion of T4 to T3 through increased action of D2 and decreased conversion of T3 to T2 through reduced action tant for TH transport in bone cells (7,12,13). Similarly, the patient evaluated by Herzovich and cols.…”
Section: Discussionmentioning
confidence: 99%
“…A prominent and common feature in MCT8 deficient patients is the failure to thrive, which may require in some cases a gastric feeding tube. Possible reasons for low weight and muscle wasting are difficulty swallowing on neurological basis, and increased metabolism due to the thyrotoxic state of peripheral tissues caused by the high serum T 3 levels [82,[85][86][87].…”
Section: Clinical Features and Course Of The Disordermentioning
confidence: 99%
“…Other MRI abnormalities reported in single cases might be non-specific. They include subtle cortical and subcortical atrophy [85], mild cerebellar atrophy [86], putaminal lesions [99] and a small corpus callosum [Dumitrescu, A.M. and Refetoff, S, unpublished data]. Increased choline and myoinositol levels and decreased N-acetyl aspartate detected by MRspectroscopy were associated with the degree of dysmyelination found on MRI [100].…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…A comparison of 12 missense mutants revealed that pathogenic MCT8 mutations may affect expression, surface translocation, or specifically the substrate transport mechanism (14). Possibly, homodimerization may also play a role that we currently do not understand (15,16). To our knowledge, no data are yet available relating structural features and transport mechanism of MCT8.…”
mentioning
confidence: 99%